2005
DOI: 10.1128/mcb.25.19.8717-8731.2005
|View full text |Cite
|
Sign up to set email alerts
|

The POU Transcription Factor Oct-1 Represses Virus-Induced Interferon A Gene Expression

Abstract: Alpha interferon (IFN-␣Alpha interferon (IFN-␣) and IFN-␤ are able to interfere with viral infection. They exert a vast array of biologic functions, including growth arrest, cell differentiation, and immune system regulation (for reviews, see references 28 and 51). This regulation extends from innate immunity to cellular and humoral adaptive immune responses. A strict control of expression is needed to prevent detrimental effects of unregulated IFN. IFN transcription is coordinately induced in human and mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 58 publications
(75 reference statements)
1
6
0
Order By: Relevance
“…This effect may result from reduced ability of the rs6495309C allele to bind Oct-1, a transcriptional factor that has been shown to be able to repress gene transcription (23)(24)(25). Consistent with this finding, our results showed that the reporter gene constructs containing the rs6495309C allele had a notably lower promoter activity compared with the constructs without rs6495309C allele.…”
Section: Discussionsupporting
confidence: 81%
“…This effect may result from reduced ability of the rs6495309C allele to bind Oct-1, a transcriptional factor that has been shown to be able to repress gene transcription (23)(24)(25). Consistent with this finding, our results showed that the reporter gene constructs containing the rs6495309C allele had a notably lower promoter activity compared with the constructs without rs6495309C allele.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, the activation of STAT-1/2 is prerequisite for the induction of IRF-1 and IRF-7 [31] . Oct-1, a member of the POU family proteins containing six classes (POU1 to POU6), was reported to regulate type I interferon transcription [32] , and was also reported to be induced in Mtb -infected human monocytes [33] . A recent study showed that Oct-1 may function as an anti-repressive regulator of those genes involved in immune and inflammatory responses when being exposed to oxidative stress [34] .…”
Section: Resultsmentioning
confidence: 99%
“…These may still be partial mechanisms with which Oct-1 is regulated in glioma tissues and IFNA8 is induced in patients with the A-genotype. Interestingly, Oct-1 can inhibit IRF-7- and IRF-3-mediated IFNA11 expression in a virus infection model 26 . Further investigations are warranted to evaluate the role of Oct-1 in the entire Type-I IFN families and anti-tumor immunity.…”
Section: Discussionmentioning
confidence: 96%